Al-Garni, A. Z., Saeed, F., Al-Garni, A. M., “Experimental and Numerical Investigation of 65-deg Delta and 65/40-deg Double-Delta Wings,” AIAA Journal of Aircraft, Vol. 45, No. 1, Jan.-Feb. 2008, pp. 71-76 - Al-Garni, Ahmed Z. (2020)
In this study, an experimental and numerical investigation was carried out to obtain lift, drag, and pitching moment data on 65-deg delta and 65/40-deg double-delta wings. The experimental tests were conducted at the KFUPM low-speed wind tunnel facility whereas the numerical tests were performed using the commercial CFD software FLUENT. Results from both experiments and numerical predictions were compared to other experimental data found in literature as well as to the theory of Polhamus. The results of comparison of surface pressure coefficient distribution and vortex breakdown location show good agreement with experiments. Overall the comparison of result shows good agreement between different experimental studies as well as good agreement with the CFD predictions and the theoretical calculations.